FENOMENA PERGESERAN PILIHAN PENDIDIKAN DASAR: ANALISIS KUALITATIF MINAT WALI MURID TERHADAP SEKOLAH DASAR SWASTA DI KABUPATEN SLEMAN - Azhar Nur Firdaus; Muhammad Iqbal Birsyada (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The increasing interest of parents in private elementary schools has become a notable phenomenon in the educational landscape of Sleman Regency. This study aims to analyze the shift in parents’ educational preferences toward private elementary schools and identify the factors influencing their decision-making process. Employing a descriptive qualitative approach, the research was conducted in Sleman Regency involving parents, school principals, and teachers as informants selected through purposive sampling. Data were collected through in-depth interviews, observations, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldaña, consisting of data condensation, data display, and conclusion drawing. The findings reveal that the shift in educational preferences is primarily influenced by four interrelated factors: academic quality and flagship programs, character and religious education, learning environment and school facilities, and school services and communication. In addition, school reputation, community recommendations, and digital media exposure strengthen parents’ trust in private schools. The study further indicates that parents no longer define a quality school solely through academic achievement, but also through its ability to develop character, provide a safe learning environment, and establish effective partnerships with families. These findings suggest that the growing preference for private elementary schools reflects not only improvements in institutional quality but also changing social constructions regarding ideal education. However, the study is limited to a qualitative investigation within selected areas of Sleman Regency and a relatively small number of informants, which may limit the generalizability of the findings to broader contexts.